Overview of the different surgical modalities for correction of caudal septal dislocation; a review article - Alqarny, Mohammed (Technium BioChemMed, 2023)
Objectives: Despite the various approaches currently available to treat CSD, this issue still needs to be resolved. Different methods and techniques to manage caudal septal dislocation with good results and according to each patient. This article reviewed the other surgical modalities for correcting caudal septum dislocation with the effectiveness of currently practiced modalities. Searching strategy: We reviewed relevant literature and used PubMed and Google Scholar. Published articles in English were included in the search. The unique and compound keywords used were caudal septum dislocation. The primary search resulted in many reports from all databases and search engines, followed by the exclusion of irrelevant articles. Findings: Different surgical modalities for correcting caudal septum dislocation have been described to correct caudal septum dislocations. Several techniques and maneuvers for surgical correction of caudal septal displacement are mentioned in the literature; nevertheless, there are different opinions and preferences regarding which approach to use. Conclusion and recommendations: An ideal caudal septoplasty should be minimally invasive and improve nasal obstruction. Surgical correction of a deviated septum can be performed using the traditional open endonasal approach, the endoscopic approach, or the open septorhinoplasty approach. In Saudi Arabia, many patients are seeking caudal septal deviation correction. However, there is a need for more trained surgeons, and it is recommended that all levels of training be considered.